STUDI KRITIS TEORI BELAJAR BEHAVIORISTIK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Farida Nur Rahma; Tatang Hidayat; Akhmad Alim (Universitas Pendidikan Indonesia, 2022)
AbstractBehavioristic learning theory is a theory that views learning as a stimulus-giving activity that produces a response. The purpose of this study is to analyze behavioristic learning theory in the perspective of Islamic education. This research uses a qualitative approach and literature study method. Based on the results of the study, the theory of behavioristic learning contains errors. Among them, this theory is part of the social sciences which should be taken from rational methods not scientific methods, learners are viewed biologically only so that they are equated with animals in learning, the learning process is ignored even though this is a decisive point in learning outcomes, but behaviorism focuses on the learning outcomes only materialistic so that in the long run it produces materialistic-opportunistic humans. In the perspective of Islamic education, the learning process in addition to using the five senses, humans also use their intellect. So that the learning process does not come to knowing but also understanding, applying, analyzing, and synthesizing.Keywords : Behavioristic, Learning, Islamic Education, Critical Studies, Learning Theory AbstrakTeori belajar behavioristik adalah teori yang memandang belajar sebagai aktifitas pemberian stimulus yang menghasilkan respon. Tujuan penelitian ini untuk menganalisis teori belajar behavioristik dalam perspektif pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif dan metode studi literatur. Berdasarkan hasil penelitian, teori belajar behavioristik mengandung kekeliruan. Di antaranya teori ini bagian dari ilmu sosial yang harusnya diambil dari metode rasional bukan metode ilmiah, pembelajar dipandang secara biologis saja sehingga disamakan dengan hewan dalam belajar, proses belajar diabaikan padahal ini poin yang menentukan dalam hasil belajar, namun behaviorisme fokus pada hasil belajarnya saja materialistik sehingga dalam jangka panjang menghasilkan manusia materialistis-oportunis. Dalam perspektif pendidikan Islam, proses belajar selain menggunakan panca indera, manusia juga menggunakan akalnya. Sehingga proses belajar tidak sampai pada mengenal saja tetapi juga memahami, mengaplikasi, menganalisis, dan mensintesis.Kata Kunci : Behavioristik, Pembelajaran, Pendidikan Islam, Studi Kritis, Teori Belajar